Ochratoxin A causes oxidative stress and cell death in rat liver - Palabiyik, S. S.; Erkekoglu, P.; Zeybek, N. D.; Kizilgun, M.; Sahin, G.; Giray, B. Kocer (Wageningen Academic Publishers, 2012)
The effect of ochratoxin A (OTA) on oxidant/antioxidant status and on histopathological changes and apoptotic cell death in livers of male Sprague-Dawley rats has been investigated. OTA (0.5 mg/kg body weight/day) was administered by oral route for 14 days. Plasma biochemical parameters, activities of liver selenoenzymes (glutathione peroxidase-1, thioredoxin reductase) and antioxidant enzymes (catalase, superoxide dismutase, glutathione S-transferase), and levels of total glutathione and thiobarbituric acid reactive substance in hepatic tissue were measured. In addition, histopathological examinations were performed and apoptotic cell death of hepatocytes was evaluated by the TdT-mediated dUTP nick-end labelling (TUNEL) assay. OTA exposure was found to induce focal necrosis of hepatocytes and mononuclear cell infiltration. Besides, exposure to OTA caused an imbalance in oxidant and antioxidant parameters in the rat liver, as evidenced by significant decreases in glutathione S-transferase activity and glutathione levels, and marked increases in concentrations of thiobarbituric acid reactive substances. Furthermore, TUNEL analysis revealed a significant similar to 2.7-fold increase in the number of TUNEL-positive liver cells of rats exposed to OTA compared to the control group. The results of this study showed that oxidative stress is at least one of the mechanisms underlying the hepatic toxicity of OTA, and that both necrosis and apoptosis are types of cell death in the hepatic toxicity of this mycotoxin.
Keywords: ochratoxin A; liver; glutathione; oxidative stress; apoptosis; necrosis